Killer immunoglobulin-like receptor (KIR) centromeric-AA haplotype is associated with ethnicity and tuberculosis disease in a Canadian First Nations cohort. - Kali Braun; Linda Larcombe; Pamela Orr; Peter Nickerson; Joyce Wolfe; Meenu Sharma (PLoS ONE, 2013)
Killer immunoglobulin-like receptors (KIR) on natural killer (NK) cells interact with other immune cells to monitor the immune system and combat infectious diseases, such as tuberculosis (TB). The balance of activating and inhibiting KIR interactions helps determine the NK cell response. In order to examine the enrichment or depletion of KIRs as well as to explore the association between TB status and inhibitory/stimulatory KIR haplotypes, we performed KIR genotyping on samples from 93 Canadian First Nations (Dene, Cree, and Ojibwa) individuals from Manitoba with active, latent, or no TB infection, and 75 uninfected Caucasian controls. There were significant differences in KIR genes between Caucasians and First Nations samples and also between the First Nations ethnocultural groups (Dene, Cree, and Ojibwa). When analyzing ethnicity and tuberculosis status in the study population, it appears that the KIR profile and centromeric haplotype are more predictive than the presence or absence of individual genes. Specifically, the decreased presence of haplotype B centromeric genes and increased presence of centromeric-AA haplotypes in First Nations may contribute to an inhibitory immune profile, explaining the high rates of TB in this population.